Prawodawstwo Konferencji Episkopatu Polski i Prymasa w zakresie sakramentów uzdrowienia - Janczewski, Zbigniew (Prawo Kanoniczne, 1998)
Two sacraments Restoration - the Penance and the Anointing of the Sick are very difficult for the life of the Church. This article shows the legislation of the Conference Episcopate o f Poland and polish primate cardinal Stefan Wyszyński in the scope of those sacraments. The Conference Episcopate is legislator in the particular Church from Council Vatican II, the primate of our country cardinal Wyszyński on the base extraordinary licenses form the pope Pius XII.